Does meter-scale snow data matter for modeling alpine plant distribution? A comparison of four data sources at two resolutions - Andreas Kollert; Kryštof Chytrý; Norbert Helm; Karl Hülber; Dietmar Moser; Johannes Wessely; Stef Lhermitte; Simon Gascoin; Andreas Mayr; Patrick Saccone; Johannes Hausharter; Michael Warscher; et al. (Ecological Modelling, 2026)

Mud volcanism and diapirism along the Japan Trench axis: evidence for a complex earthquake plumbing system on the down-going plate - Myra Keep; Troy Rasbury; Cecilia McHugh; Michael Strasser; Ken Ikehara; Charlotte Pizer; Yasuyuki Nakamura (Marine and Petroleum Geology, 2025)

Strong earthquake in a low seismicity area of the European Southern Alps during Roman Times – A lacustrine paleoseismic evaluation - Markus Niederstätter; Katleen Wils; Arne Ramisch; Jean Nicolas Haas; Hannah Pomella; Sönke Szidat; Michael Strasser; Jasper Moernaut (Quaternary Science Reviews, 2025)

Strong magnetism and geochemical characteristics of sediment in Challenger Deep and their indications for sources - KaiWei Wang; YongHong Wang; QiuYu Yue; XiaoHua Zhang; JiWen Liu; Chunhui Xiao; Toshiya Kanamatsu; Michael Strasser; Rui Bao (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Clustered slumping in the northern South China Sea: Implications for chronology and geohazards - Yin Lu; Ed L. Pope; Qiliang Sun; Michael Strasser (Global and Planetary Change, 2025)

Japan Trench event stratigraphy: First results from IODP giant piston coring in a deep-sea trench to advance subduction zone paleoseismology - Michael Strasser; Ken Ikehara; Charlotte Pizer; Takuya Itaki; Yasufumi Satoguchi; Arata Kioka; Cecilia McHugh; Jean-Noel Proust; Derek Sawyer; J. Everest; L. Maeda; K. Hochmuth; et al. (Marine Geology, 2024)

Background concentrations of airborne, culturable fungi and dust particles in urban, rural and mountain regions - Doris Haas; Mihaela Ilieva; Theresa Fritz; Herbert Galler; Juliana Habib; Angela Kriso; Michael Kropsch; Petra Ofner-Kopeinig; Franz F. Reinthaler; Andreas Strasser; Eduard Zentner; Michael Schalli (Science of The Total Environment, 2023)

Large‐scale mass movements recorded in the sediments of Lake Hallstatt (Austria)–evidence for recurrent natural hazards at a UNESCO World Heritage site - Stefan Lauterbach; Michael Strasser; Kerstin Kowarik; Hans Reschreiter; Gerhard W. Mandl; Christoph Spötl; Birgit Plessen; Achim Brauer (Journal of Quaternary Science, 2023)
The Bronze to Iron Age underground salt mining complex of Hallstatt (Austria) is widely recognised for its cultural importance and wealth of archaeological artefacts. However, while the daily life in the salt mines is archaeologically well documented and environmental effects of the mining activity have been investigated recently, the impact of natural hazards on the prehistoric mining community is still poorly understood. For instance, while it is well established that the prehistoric underground mines have repeatedly been destroyed by large‐scale mass movements, only little is known about the characteristics and extent of these events as well as about mass‐movement recurrence during more recent times. To shed light on past mass‐movement activity in the vicinity of the Hallstatt salt mines, we investigated sediment cores from adjacent Lake Hallstatt. Within the regular lake sediments we identified three large‐scale event deposits, which are interpreted to originate from spontaneous or seismically induced mass movements in the mid‐19th and late 9th century ce and the mid‐4th century bce. While the age of the latter event is in good agreement with the abandonment of the famous Iron Age cemetery at Hallstatt, the younger events indicate that large‐scale mass movements also occurred repeatedly during the Common Era.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

A tsunamigenic delta collapse and its associated tsunami deposits in and around Lake Sils, Switzerland - Valentin Nigg; Stephan Wohlwend; Michael Hilbe; Benjamin Bellwald; Stefano C. Fabbri; Gregory F. de Souza; Florian Donau; Reto Grischott; Michael Strasser; Flavio S. Anselmetti (Natural Hazards, 2021)
Large lacustrine mass movements and delta collapses are increasingly being considered as potential tsunamigenic sources and therefore hazardous for the population and infrastructure along lakeshores. Although historical reports document tsunami events in several lakes in Switzerland, and although the propagation of lake tsunamis has been studied by numerical wave modeling, only little is known about on- and offshore lacustrine tsunami deposits. In Lake Sils, Switzerland, a large prehistoric mass-movement deposit originating from the Isola Delta with a minimum estimated volume of 6.5 × 10 6 m 3 and a basinal thickness of > 6 m in the seismic record has been identified by previous studies and radiocarbon dated to around 700 Common Era. Here, we combine (i) comprehensive sedimentological investigation of sediment cores recovered from the on- and offshore settings, (ii) mineralogical fingerprinting of the inflows from key catchments to characterize sediment provenance, and (iii) numerical tsunami modeling, to test the hypothesis of a tsunamigenic delta collapse in Lake Sils. We observe a clastic event deposit consisting of coarse-grained, fining-upward sand overlying an organic-rich peat deposit in the shallow water. This layer thins and fines landward on the coastal plain. Toward the deeper water (20–40 m), the deposit transforms into a thicker and more heterogeneous sediment package with multiple sequences of fining-upward sand and a well-pronounced clay cap at the top. Radiocarbon dating of the peat underlying the event deposit yields a maximum age of 225–419 calibrated Common Era. The tsunami models, which indicate wave heights reaching up to 5 m, simulate areas of inundation that coincide with the location of event deposits. Based on our results, we propose that the historically undocumented Isola Delta collapse generated a basin-wide tsunami that inundated the lakeshore, transporting large amounts of unconsolidated sediment along the lakeshore toward the coastal plain and into the deeper lake basin.

A database of potential paleoseismic evidence in Switzerland - Katrina Kremer; Gabriela Gassner-Stamm; Remo Grolimund; Stefanie B. Wirth; Michael Strasser; Donat Fäh (Journal of Seismology, 2020)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Effects of elastic band resistance training and nutritional supplementation on muscle quality and circulating muscle growth and degradation factors of institutionalized elderly women: the Vienna Active Ageing Study (VAAS) - Marlene Hofmann; Barbara Schober-Halper; Stefan Oesen; Bernhard Franzke; Harald Tschan; Norbert Bachl; Eva-Maria Strasser; Michael Quittan; Karl-Heinz Wagner; Barbara Wessner (European Journal of Applied Physiology, 2016)

The role of sediment composition and behavior under dynamic loading conditions on slope failure initiation: a study of a subaqueous landslide in earthquake-prone South-Central Chile - Gauvain Wiemer; Jasper Moernaut; Nina Stark; Philipp Kempf; Marc De Batist; Mario Pino; Roberto Urrutia; Bruno Ladrón de Guevara; Michael Strasser; Achim Kopf (International Journal of Earth Sciences, 2015)

New constraints on oceanographic vs. seismic control on submarine landslide initiation: a geotechnical approach off Uruguay and northern Argentina - Fei Ai; Michael Strasser; Benedict Preu; Till J. J. Hanebuth; Sebastian Krastel; Achim Kopf (Geo-Marine Letters, 2014)

Mid-Quaternary decoupling of sediment routing in the Nankai Forearc revealed by provenance analysis of turbiditic sands - Muhammed O. Usman; Hideki Masago; Wilfried Winkler; Michael Strasser (International Journal of Earth Sciences, 2014)

The energy flux theory 35 years later: formulations and applications - Merope Tsimilli-Michael; Reto J. Strasser (Photosynthesis Research, 2013)

Contributions of high- and low-quality patches to a metapopulation with stochastic disturbance - Carly A. Strasser; Michael G. Neubert; Hal Caswell; Christine M. Hunter (Theoretical Ecology, 2012)

Sediment dynamics and geohazards off Uruguay and the de la Plata River region (northern Argentina and Uruguay) - Sebastian Krastel; Gerold Wefer; Till J. J. Hanebuth; Andrew A. Antobreh; Tim Freudenthal; Benedict Preu; Tilmann Schwenk; Michael Strasser; Roberto Violante; Daniel Winkelmann (Geo-Marine Letters, 2011)

Mapping basin-wide subaquatic slope failure susceptibility as a tool to assess regional seismic and tsunami hazards - Michael Strasser; Michael Hilbe; Flavio S. Anselmetti (Marine Geophysical Research, 2011)

Response of endangered plant species to inoculation with arbuscular mycorrhizal fungi and soil bacteria - Szymon Zubek; Katarzyna Turnau; Merope Tsimilli-Michael; Reto J. Strasser (Mycorrhiza, 2009)

Erosional processes, topographic length-scales and geomorphic evolution in arid climatic environments: the ‘Lluta collapse’, northern Chile - Michael Strasser; Fritz Schlunegger (International Journal of Earth Sciences, 2005)

Heterologous protein production in yeast - Gerd Gellissen; Karl Melber; Zbigniew A. Janowicz; Ulrike M. Dahlems; Ulrike Weydemann; Michael Piontek; Alexander W. M. Strasser; Cornelis P. Hollenberg (Antonie van Leeuwenhoek, 1992)